Specificity of Shestov’s interpretation of existentialtheological views of Kierkegaard - Ševčenko, Serhij Ivanovyč (Ukrai͏̈ns'ke relihijeznavstvo, 2015)
Specificity of Shestov’s interpretation of existentialtheological views of Kierkegaard. This article reveals the problem of understanding of Soren Kierkegaard’s specific religious existentialism by Lev Shestov. The author argues that Shestov failed to adequately understand the Kierkegaard’s indirect discursive method. Therefore, Shestov is inadmissible interpretation of Kierkegaard of canonical Christianity.